A case report of anaplastic thyroid carcinoma transformed from small papillary carcinoma successfully detected by ultrasonography in its early stage with review of literature - Hiroshi Arimitsu; Yui Nishijima; Naoyuki Higaki; Hitoshi Noguchi; Shinya Uchino; Tsukasa Murakami (Endocrine Journal)
An 82-year-old woman was referred to our hospital because of a suspicious thyroid nodule. She was diagnosed with papillary microcarcinoma with a maximum diameter of 9 mm based on ultrasonography and fine-needle aspiration (FNA) cytology. She preferred observation without surgery. Her papillary carcinoma grew gradually and reached a maximum diameter of 19 mm after 23 months. At that time, ultrasonography showed an apparent change in the shape of the nodule as well as in its diameter. At the initial ultrasound examination, papillary microcarcinoma was demonstrated as a hypoechoic solid nodule with an irregular shape. No punctuate microcalcifications were shown. After 23 months, the preexisting nodule had expanded toward the common carotid artery. The expanded portion was round and well demarcated. FNA revealed that the expanded portion consisted of anaplastic thyroid carcinoma. She underwent hemithyroidectomy and lymph node dissection of the central compartment. She remained in good health for 18 months after surgery. Anaplastic thyroid carcinoma is generally found as an aggressive large tumor, and the ultrasound appearance of small anaplastic thyroid carcinoma is poorly understood at present. We successfully detected anaplastic transformation in the early period by ultrasonography and FNA. When observation is indicated for small papillary thyroid carcinoma, the change in the shape of the nodule as well as in its diameter should be carefully monitored by ultrasonography. FNA should be performed at a proper site on the nodule to avoid overlooking anaplastic transformation, as resection following the early detection of anaplastic transformation might bring a favorable prognosis.